Publikasi Artikel Ilmiah sebagai Kebutuhan Berprestasi Mahasiswa: Studi Kasus Kelas Menulis FUSA UIN Mataram - Wahyudin Darmalaksana; Putri Anditasari; Hidayatul Fikra; Susanti Vera; Fitriani Fitriani (Gunung Djati Conference Series, 2024)
This study aims to discuss the need for achievement in the student environment in the publication of scientific articles through the formation of the "Kelas Menulis " of the Faculty of Ushuluddin and Religious Studies, State Islamic University of Mataram. This study uses a qualitative approach by applying descriptive-analytical methods. The formal object of this study is the theory of the need for achievement in the phase of writing scientific articles within the framework of the scientific publication continuum project. While the material object of this study is the practice of writing scientific articles in the environment of academic writing ambassador students. The results of the discussion show that academic writing ambassadors have fulfilled the aspects of the theory of the need for achievement in the phase of practicing writing scientific articles, namely first, the desire to exceed, second, achieving standards, and third, hard work to achieve achievements. This study concludes that academic writing ambassadors in the "Kelas Menulis" of the Faculty of Ushuluddin and Religious Studies, State Islamic University of Mataram are considered to have fulfilled the theory of the need for achievement in the phase of practicing writing scientific articles.